O melodrama e a política: um estudo sobre a adaptação de A Vida Invisível para o cinema - Rodrigues, Laís Torres (Universidade Federal de São Carlos, 2023)
This work explores the adaptation of the book A Vida Invisível de Eurídice Gusmão (2016), by Martha Batalha, for the film A Vida Invisível (2019), by Karim Aïnouz. Starting from the filmic analysis of four sequences, the study explores melodrama as a tool of adaptation and intermediality as ways of approaching the analysis, proposing new interpretations for the film. We also approach the permanence of melodrama and its political use, and seek to undertake new perspectives on the film to expand the analysis of policies of representation of the feminine in Brazilian cinema.
Melodrama and politics: a study regarding the adaptation of The Invisible Life of Eurídice Gusmão into film
Keywords: Adaptação; Melodrama; Intermidialidade; Literatura; Karim Aïnouz; Análise fílmica; Cinema brasileiro; Adaptation; Intermediality; Film analisys; Brazilian cinema; Literature; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA